Orbital maneuvers between the Lagrangian points and the primaries in the Earth-Sun system - Prado,Antônio F. B. Almeida (2006)
This paper is concerned with trajectories to transfer a spacecraft between the Lagrangian points of the Sun-Earth system and the primaries. The Lagrangian points have important applications in astronautics, since they are equilibrium points of the equation of motion and very good candidates to locate a satellite or a space station. The planar circular restricted three-body problem in two dimensions is used as the model for the Sun-Earth system, and Lamaître regularization is used to avoid singularities during the numerical integration required to solve the Lambert's three-body problem. The results show families of transfer orbits, parameterized by the transfer time.